(untitled) (Bangladesh Journal of Plastic Surgery, 2011)
Hidradenitis suppurativa is a rare non-contagious, chronic, relapsing suppurativa cicatrizing skin disease that most commonly affects areas of the body bearing apocrine sweat glands or sebaceous glands, such as the underarms, breasts, inner thighs, groin and buttocks, which manifests itself as a clusters of chronic abscesses, sinus, fistulas or multilocalised infections. This physically, psychologically, and socially disabling disease is extremely painful to touch and may persist for years with occasional to frequent periods of inflammation, culminating in drainage, often leaving open wounds that will not heal. As it is considered as a rare disease the incidence rate is not well known, but estimated in a range between 1:24(4.1%) and 1:600(0.2%) in which the post-pubertal females are more affected than males. The exact cause of hidradenitis suppurativa remains unclear. What is understood is that the condition is a disorder of follicular occlusion. With genetic predisposition, obesity, hormonal influences etc contribute to the causation of the disease .There is no cure for hidradenitis suppurativa. But early treatment can help to manage the symptoms and to prevent new lesions from developing. Long term antibiotics are the treatment of choice in early stage, but relapsing and recurrent cases may need surgical interventions. Here we present an 18 year old girl suffering from this disabling disease in both axillas, sternal and submammary region for six years. She was treated inadequately with oral antibiotics and surgical intervention in the form of incision and drainage done previously. We treated her with wide excision of the diseased skin and defect reconstructed with local advancement flap. Histopathological study of the excised skin revealed Hidradenitis suppurativa. Key word : Epidermis/surgery; vitiligo/therapy; transplantation alutologous DOI: http://dx.doi.org/10.3329/bdjps.v1i2.8803 BDJPS 2010; 1(2): 30-37